Ultrasound-guided continuous radiofrequency ablation of the proximal greater occipital nerve is effective in refractory occipital neuralgia: a retrospective cohort study - Turan, Suna Aşkın; Aydın, Şenay; Can, Ezgi (Arquivos de Neuro-Psiquiatria, 2025)
Pain in occipital neuralgia (ON) originates from the upper cervical nerves converging with the trigeminal complex. Greater occipital nerve (GON) blocks and radiofrequency treatments can be used in refractory ON.To assess the efficacy of ultrasound-guided proximal greater occipital nerve (PGON) continous radiofrequency ablation (CRFA) in ON throughout 1 year.We analyzed data from medical records and headache diaries. Before the intervention and 1, 3, 6, and 12 months after the intervention, at each appointment we evaluated the headache intensity through the 11-point Numeric Rating Scale (NRS-11), the headache disability, through the Six-Item Headache Impact Test (HIT-6), as well as the headache days per month. Treatment efficacy was determined by NRS-11 score < 4 at 12 months.A total of 18 patients were analyzed. The mean initial NRS-11 score was of 8.78 ± 0.732. At least 50% of pain reduction was noted in all patients at 6 months, and in 66% patients at 12 months. The frequency of attacks was correlated to poor response (r = 0.598; p = 0.009). The efficacy of the diagnostic block was correlated to successful response (r = -0.789; p = 0.001). For the categorical variables, the electric shock pain was associated with NRS-11 score ≥ 4 (p = 0.041), and lancinating pain was associated with NRS-11 score < 4 at 12 months (p = 0.031).Ultrasound-guided PGON CRFA in refractory ON significantly reduced pain for up to 1 year. The initial frequency of attacks, electric shock like pain, and reduced response to diagnostic block were associated with reduced response.
Keywords: Neuralgia; Headache; Radiofrequency Ablation; Nerve Block; Ultrasonography, Interventional; Pain Measurement; Treatment Outcome